GHAFUR GHULAM'S ARTISTIC PRINCIPLE IN ILLUMINATING THE TRUTH OF THE TIME - Nasiba Bozorova; Yarmuhammat Kh. Madaliev (American Journals Publishing, 2023)
The Jesuits and the poet constantly perform the Davring ilgor vakillari sanalgan. Siiy zharain, the ex-Soviet government adopted a People-oriented leadership, talent, el horasidan Khurmati julida yahshigina foidalangan. During the meeting, the sides expressed satisfaction with the development of cooperation between Tajikistan and China. Tajikistan, Tajikistan and Tajikistan. But bedii ijodkorga the truth is that jeritish may be beradi, a symbol, a majozy way of thinking known as bir Petra Real vakelik book and kelajakka yadi.Article Uzbek literary studies "Gafur Rabning” Shum bola " to tell the story of the life, epoch, political ideology of the nation, the life of the influence of uziga basically describes yeritilgan
Keywords: izhimoy life, epoch, Syrian ideology, literature, badiy izhod, Gafur rab, “shuma bola